Students’ Perception on Learning English For Law Faculty Students at University of Batanghari Jambi - Suyadi Suyadi; Siti Aisyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study is determined to analyze the negative and positive perceptions of Law Faculty students in learning English as a compulsory subject. There were 30 Law Faculty students at Second Semester Academic Year 2020/2021 involved in this research. The study adopted survey approach by giving questionnaire of ‘Yes’ or ‘No’ to explore five (5) indicators motivation, learning strategies, feeling, communication, and knowledge related to learning English. The participants of the study were Second Semester Students of Law Faculty of University of Batanghari. A convenient purposive sampling was used to allocate students’ perception on learning English. The findings revealed that 83% of students shared positive perception on learning English at Law Faculty with the reasons that English could be useful for law practitioner. While, 27% of students shared negative perception as they have personal reasons such as; do not like English language to be profession, English is difficult to learn, and English is difficult to pronoun.